The perceptions of employability skills transferred from academic leadership classes to the workplace: a study of the FHSU leadership studies certificate program - Arensdorf, Jill (Kansas State University, 2009)
Employers want to hire students with the appropriate skill set for the job. These skills include communication, problem-solving, and teamwork skills (Billing, 2003; Shivpuri & Kim, 2004). The purpose of this study was to evaluate whether students perceive themselves to be transferring employability skills learned in the Fort Hays State University (FHSU) Leadership Studies Certificate Program to the workplace. The Leadership Studies Certificate Program consists of three academic leadership courses; Introduction to Leadership to Leadership Concepts, Introduction to Leadership Behaviors, and Fieldwork in Leadership Studies. Three groups were created for the purpose of the study. Group one served as a control group and consisted of participants who had not taken a leadership course at FHSU. Group two consisted of a sample of students who had completed one or two courses out of the Leadership Studies Certificate Program. Participants who had completed the entire Leadership Studies Certificate made up group three. The study sought to evaluate the participants’ perceptions with regard to the level of importance of identified employability skills, as well as their level of competence in performing each of the employability skills. The study also sought the supervisors’ perceptions of the study participants in each of the three groups. Employability skills studied were problem-solving skills, communication skills, teamwork skills, change and innovation behaviors, ability to manage self, and being civic-minded. Study participants and their supervisors both perceived the ability to manage self as the most important skill in the workplace. Findings showed no differences between participant groups with respect to the perceived importance and competence levels on each of the six employability skill constructs. Supervisors of Leadership Studies Certificate recipients deemed communication skills as more important to their employee’s job than supervisors who employed students who had never taken an FHSU leadership course. No differences were found between supervisor groups with respect to perceived importance and competence on the remainder of the employability skills. Further research should be conducted on the Leadership Studies Certificate Program to understand its impact on students’ development of employability skills. Upon conclusion of this analysis, possible curriculum modifications should be considered.
Keywords: Leadership Education; Employability Skills; Education, General (0515)